Panoramic radiographs for identifying individuals with undetected osteoporosis - Akira Taguchi (Elsevier, 2009)
Numerous panoramic radiographs are taken annually to examine dental diseases, and using them for triaging individuals with general skeletal bone diseases, such as osteoporosis, would be economical and beneficial as dentists could refer these patients to medical professionals for further examination. Since the early 1990s, several studies have been performed regarding the utility of panoramic radiographs in triage screening for osteoporosis in dental clinics. Cortical indices of the mandible on panoramic radiographs, such as cortical width and cortical shape, are significantly associated with bone mineral density (BMD) of the general skeleton, biochemical markers of bone turnover and risk of osteoporotic fractures in postmenopausal women as well as elderly men. In prospective clinical trials, about 95% of postmenopausal women identified by trained general dental practitioners using cortical shape category on panoramic radiographs had low skeletal BMD or osteoporosis. Panoramic radiography indices may be likely useful triage screening tools for identifying individuals with an increased probability of having low skeletal BMD, osteoporosis and osteoporotic fractures. However, further investigations should be conducted worldwide to determine whether these indices are acceptable for triaging individuals with osteoporosis and referring them to medical professionals.